Social innovation in access to healthcare: community-based health insurance among Senegalese migrants in Spain - Modou Diop; Rita Sobczyk (BMC Health Services Research)
Abstract Background In several European Union countries, undocumented migrants face significant barriers to accessing universal healthcare. In Spain, Royal Decree-Law 16/2012 introduced restrictions that limited undocumented migrants’ access to healthcare services, offering only emergency, maternal, and paediatric care. The implementation of this law created significant disparities in access to healthcare across regions. Although the law was later amended and some regions introduced alternative programs to restore access, disparities in healthcare access remain. This study aims to analyse the contribution of Community-based Health Insurance (CBHI), developed by migrant organisations, to improving healthcare access for Senegalese migrants in Spain. Methods We conducted 28 in-depth interviews and one discussion group across various Spanish localities between 2019 and 2022 to examine how CBHI influences healthcare access among Senegalese migrants. Using purposive sampling, we ensured diversity in participants’ administrative status, sociodemographic profiles, and employment situations. Grounded theory was employed to analyse the data, focusing on the social innovation and organizational dynamics of the tontines, as well as the role migrant organizations play in facilitating healthcare access through these solidarity-based financial mechanisms. Results The findings show that CBHI has emerged as a socially innovative, collective response to unmet medical needs. Through the mobilization of community funds, Senegalese migrant organizations have filled gaps left by the public and private healthcare systems, offering a crucial alternative for those excluded from formal services. Our findings also highlight the rise of transnational healthcare trends, as community insurance funds are allocated not only for healthcare in Spain but also for return and care in Senegal. This dual focus demonstrates the importance of these grassroots microfinance initiatives in enhancing healthcare access for migrants. Conclusions CBHI through tontines represents an essential community-led solution that enhances healthcare access for undocumented Senegalese migrants in Spain. Migrant organizations serve as key intermediaries, using solidarity-based microfinance models to bridge healthcare gaps left by restrictive policies. These initiatives demonstrate the capacity for grassroots innovation to address structural barriers to healthcare access in both destination and origin countries, providing a model for other migrant communities facing similar challenges.